2005
DOI: 10.1111/j.1744-9987.2005.00285.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Cytapheresis for Antineutrophil Cytoplasmic Antibody‐associated Renal Vasculitis and Its Effect on Anti‐inflammatory Factors

Abstract: To evaluate the efficacy of cytapheresis for the treatment of rapidly progressive glomerulonephritis (RPGN) caused by myeloperoxidase antineutrophil cytoplasmic antibody (MPO-ANCA)-associated vasculitis, the renal prognosis and the mortality rate at 1 year after treatment were compared between a Cytapheresis Group and a Steroid Pulse Group. The Cytapheresis Group included 10 patients who were treated with cytapheresis and oral corticosteroids. Five had granulocytapheresis with the Adacolumn (Japan Immuno Resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Our study shows that the most important cause of death of patients who died between 3 and 12 mo of follow-up was therapy-related infection. Recent studies also showed that the main cause of death in ANCA-associated glomerulonephritis is treatment-related infectious complication (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Our study shows that the most important cause of death of patients who died between 3 and 12 mo of follow-up was therapy-related infection. Recent studies also showed that the main cause of death in ANCA-associated glomerulonephritis is treatment-related infectious complication (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that LCAP is more effective than steroid-pulse treatment for reduction of glomerular injury due to RPGN, as an effect of its selective removal of CD8 and CD14 cells. In addition, Hasegawa et al [36] also reported the efficacy of cytapheresis for the treatment of RPGN caused by myeloperoxidase (MPO)-ANCA-associated vasculitis, in comparison between a cytapheresis group and a steroid pulse group. In their study, the cytapheresis group included 10 patients who were treated by GCAP with the Adacolumn in 5 patients and other 5 patients by LCAP with the Cellsorba.…”
Section: Lcap or Gcap For Glomerular Diseases Nephrotic Syndrome Andmentioning
confidence: 99%
“…Although the pathophysiological mechanism of ANCA‐associated vasculitis has not been clearly elucidated, in vitro studies have shown that ANCA can activate TNF‐α‐primed polymononuclear and mononuclear cells to undergo a respiratory burst with the release of reactive oxygen species, as well as degranulation of azurophil granules and secretion of pro‐inflammatory cytokines (10). As for the mechanism of the action of cytapheresis, we previously reported that productivity of inflammatory cytokines from mononuclear cells was reduced after treatment (11) and that sTNFR1, sTNFR2, IL‐1Ra, and IL‐10 levels decreased after 1 h of cytapheresis (12). In the present study we measured sTNFR1, sTNFR2 and IL1Ra at the start of cytapheresis, at completion of the procedure, and 2 h after completion.…”
Section: Discussionmentioning
confidence: 99%